Building Tana Toraja Towards a Smart City - Lisa Kurniasari Wibisono; Mey Enggane Limbongan; Dina Ramba (Green Publisher Indonesia, 2024)
Tana Toraja is one of the districts located in the northern part of South Sulawesi. Currently, the Tana Toraja District plans to build at least 31 4G cellular network towers in 10 sub-districts to equalize the development of telecommunication infrastructure in the area. Therefore, this research is conducted to provide recommendations to the Tana Toraja District Government regarding the optimization of village development policies using information and communication technology approaches and to encourage the implementation of digital empowerment in public services. The results of this study indicate that the approach that can be used by the Tana Toraja District Government in building towards a smart city includes: developing infrastructure that can support smooth internet connectivity throughout the area and developing public services towards digitalization, such as e-Administration, e-Transportation, e-Health, e-Money, and e-Report. However, the increasing offering of technology-based public services to be developed in the Tana Toraja District will pose significant challenges, particularly in terms of human resources, financing, and data security.